Experience in Intention to Buy: Engagement as a Mediation in Retail Skincare Product - Gabriella Jodie Patricia Wijanna; Gede Ariadi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The emergence of the number of skincare cosmetic retailers in Salatiga, Central Java, is one of the factors in which the percentage of women who are aware of the importance of skin health is increasing, especially since the causes of skin problems are currently various. It makes one of the retailers in Salatiga, namely G&G skin care cosmetics store, need to strengthen relationships with their customers to survive and achieve business excellence amid a competitive skincare market. This research was lifted from the curiosity of researchers regarding the significant influence of brand experience on the intention to buy products through G&G stores by using brand involvement as mediation. Data collection was carried out by distributing questionnaires to 100 respondents who had made purchases at G&G cosmetics retail at least once. The sample used in this research is judgmental sampling. The structural Equation Modeling (SEM) method with Partial Least Square (PLS) was applied in this study. Then, the result of this study shows that brand experience has a significant effect on the intention to buy a product, with the three indicators of brand involvement as mediation. Moreover, the results also show that G&G retail skincare brands need to increase their activation in brand engagement to attract and maintain relationships with their consumers in the long term.